2002
DOI: 10.1021/ma0119833
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Structure of Polyelectrolyte Multilayer Films Exhibiting a Linear and an Exponential Growth Regime: An in Situ Atomic Force Microscopy Study

Abstract: We report here on the structural characterization of polyelectrolytes multilayer films formed by poly(l-glutamic acid) and poly(l-lysine) (PGA/PLL). The growth of this system is compared to that of poly(styrenesulfonate)/poly(allylamine hydrochloride) (PSS/PAH) multilayers by means of in situ atomic force microscopy (AFM) and by optical waveguide lightmode spectroscopy (OWLS). In contrary to the (PSS/PAH) i films that are growing linearly with the number of deposited layer pairs i, optical data evidenced that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
547
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 495 publications
(615 citation statements)
references
References 27 publications
46
547
3
Order By: Relevance
“…Fig. S1 shows the exponential increase in thickness and mass with layer number, as expected for exponentially growing PLL/PGA multilayer films (41). The deposition of BMP 2 and TGFβ 1 on the underlying PLL layers results in an increase in both thickness and mass, which indicates the successful embedding of the negatively charged proteins within the film architecture.…”
Section: Resultssupporting
confidence: 56%
“…Fig. S1 shows the exponential increase in thickness and mass with layer number, as expected for exponentially growing PLL/PGA multilayer films (41). The deposition of BMP 2 and TGFβ 1 on the underlying PLL layers results in an increase in both thickness and mass, which indicates the successful embedding of the negatively charged proteins within the film architecture.…”
Section: Resultssupporting
confidence: 56%
“…the material adsorbed on the electrode increases more than linearly with the number of deposited layers. This nonlinear or exponential growth of the film was also observed previously in the formation of PLL/PGA films on other substrates [13,18,19] and in films comprising PLL or PGA, for example, PLL/hyaluronic acid [20] and PGA/poly(allylamine hydrochloride) [21] multilayer films. Previous studies on polyelectrolyte LbL multilayer films have demonstrated that the growth of the multilayer film is entropy driven and an endothermic complexation process of PLL/PGA corresponds to the exponential growth of the film [22].…”
Section: Pll/pga Multilayer Film Assemblysupporting
confidence: 82%
“…These positively charged substrates were used for polyelectrolyte deposition beginning with a polyanion (PSS in the present case). 25 LbL assembly of PSS/PAH on functionalized glass or SIF substrates was carried out manually. The substrates were immersed in a PSS solution for 20 min, followed by a wash in water for 5 min, and immersed again in the PAH solution for 20 min, followed a wash for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18][19] A detail understanding of the MEF and its distance dependence nature is vital for its potential application in biomedical sensing. [20][21][22] Layer-by-layer (LbL) assembly [23][24][25][26][27][28][29][30][31][32][33][34][35][36] is based on the sequential adsorption of polycations and polyanions from dilute aqueous solution onto a solid substrate as a consequence of the electrostatic interaction and complex formation between oppositely charged polyelectrolytes. Starting from a functionalized solid substrate, it is possible to adsorb a variety of charged species ranging from polyelectrolytes, nanoparticles, and ionic dyes to many biological agents such as viruses, proteins, and DNA.…”
Section: Introductionmentioning
confidence: 99%